Direct action of endocrine disrupting chemicals on human sperm. (12th May 2014) - Schiffer, Christian; Müller, Astrid; Egeberg, Dorte L; Alvarez, Luis; Brenker, Christoph; Rehfeld, Anders; Frederiksen, Hanne; Wäschle, Benjamin; Kaupp, U Benjamin; Balbach, Melanie; Wachten, Dagmar; Skakkebaek, Niels E; et al.
Abstract Synthetic endocrine disrupting chemicals (EDCs), omnipresent in food, household, and personal care products, have been implicated in adverse trends in human reproduction, including infertility and increasing demand for assisted reproduction. Here, we study the action of 96 ubiquitous EDCs on human sperm. We show that structurally diverse EDCs activate the sperm‐specific CatSper channel and, thereby, evoke an intracellular Ca2+ increase, a motility response, and acrosomal exocytosis. Moreover, EDCs desensitize sperm for physiological CatSper ligands and cooperate in low‐dose mixtures to elevate Ca2+ levels in sperm. We conclude that EDCs interfere with various sperm functions and, thereby, might impair human fertilization.